2003
DOI: 10.1002/art.11307
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase gene polymorphisms in giant cell arteritis

Abstract: Objective. To examine potential associations of the Glu/Asp 298 polymorphism in exon 7 and the 4a/b polymorphism in intron 4 of the endothelial nitric oxide synthase (eNOS) gene with susceptibility to and clinical expression of giant cell arteritis (GCA), particularly in patients with versus those without ischemic complications.Methods. Ninety-one consecutive patients with biopsy-proven GCA, who were residents of Reggio Emilia, Italy, and 133 population-based controls from the same geographic area were genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
38
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 33 publications
8
38
0
Order By: Relevance
“…ab genotype (b) of the 4b/a polymorphism and LN function. Since glutamate and aspartate are conservative substitutions, this polymorphism may serve as a marker for a functional effect elsewhere in the eNOS gene or in the vicinity of the eNOS gene [22]; for example, it may be in linkage disequilibrium with regulatory polymorphisms in the same haplotype. Furthermore, it has been suggested that the G894T polymorphism generates protein products susceptible to cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…ab genotype (b) of the 4b/a polymorphism and LN function. Since glutamate and aspartate are conservative substitutions, this polymorphism may serve as a marker for a functional effect elsewhere in the eNOS gene or in the vicinity of the eNOS gene [22]; for example, it may be in linkage disequilibrium with regulatory polymorphisms in the same haplotype. Furthermore, it has been suggested that the G894T polymorphism generates protein products susceptible to cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Restriction digestion was performed in a total volume of 25 μl reaction mixture containing 10 μl PCR product and 2 U BanII restriction endonuclease (Roche Diagnostics GmbH, Germany). Reaction mixtures were incubated at 37°C overnight and the genotyeNOS polymorphism in gastric cancer pes were determined by agarose gel electrophoresis of restriction digests in 2% agarose gel containing 0.5 μg/ml ethidium bromide (17).…”
Section: Determination Of Enos Genotypesmentioning
confidence: 99%
“…25,26 Several variations in the human genome have been linked to increased risk of cardiovascular disease, and some of these are known to relate specifically to endothelium-relevant processes. [27][28][29][30][31][32] Here, we focused on two genetic variations (in NOS3 and ACE) known to occur with high frequency and known to be statistically associated with various forms of vascular disease, including diabetesrelated cardiovascular complications. Using this approach we were able to test the hypothesis that the presence of the NOS3 Glu298Asp genotype, or the ACE insertion/deletion genotype, affected the endothelial response to glycaemic stress or 3NT exposure.…”
Section: Discussionmentioning
confidence: 99%